The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su141912310
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Electronic Customer Relationship Management System Success: The Mediating Role of Customer Satisfaction

Abstract: This study evaluated the relationships among variables in electronic customer relationship management (e-CRM) success. The purpose of this paper is to examine the effect of technological readiness, privacy, COVID-19, customer pressure, trust, level of service quality, and customer satisfaction. Quantitative research methods were applied in examining the causal associations among the primary variables of the study. We used a sample approach called purposive sampling. Data was obtained from 390 completed questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 121 publications
3
13
0
Order By: Relevance
“…The current study also emphasizes on effective CRM system which can bring competitive advantage to business which has been acknowledged (16) . The mediating role of CRM in the relationship between trust and system effectiveness has been highlighted by (17) which is also in line with present study. In contrast with the outcome of (18) , which show that product pricing and packaging have a significant relationship with the buyer's decision process, however, current study results indicate that DBB has a positive impact on Risk Factors associated with digital buying.…”
Section: Mediation Analysissupporting
confidence: 91%
“…The current study also emphasizes on effective CRM system which can bring competitive advantage to business which has been acknowledged (16) . The mediating role of CRM in the relationship between trust and system effectiveness has been highlighted by (17) which is also in line with present study. In contrast with the outcome of (18) , which show that product pricing and packaging have a significant relationship with the buyer's decision process, however, current study results indicate that DBB has a positive impact on Risk Factors associated with digital buying.…”
Section: Mediation Analysissupporting
confidence: 91%
“…It has also been found that the trust in the service provider will positively impact satisfaction, as satisfaction is a consequence of trust (Ambarwati et al, 2022). Furthermore, customer satisfaction was proven to be impacted by the level of trust customers have in the service provider, as they are positively linked (Al-Bashayreh et al, 2022). Therefore, the following third hypothesis is put forth: H03.…”
Section: Patient Trust and Patient Satisfactionmentioning
confidence: 99%
“…Trust encourages the parties involved to preserve and invest in the relationship, and cooperate rather than act opportunistically (Moreira and Silva, 2015). Al-Bashayreh et al. (2022) asserted that the establishment of trust with customers is a crucial step in any business, while Andaleeb et al.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffee culture and cafés define identity and social styles along with economic growth, workplace culture, sustainability awareness, and knowledge creation. Be it for business meetings, team socialization, digital and e-coffees, attractive coffee perks, or as a musthave workplace experience [5,6]-coffee has it all. It not only energizes for work, but also provides family timeout, leisure, and personal wellbeing experiences at cafés.…”
Section: Introductionmentioning
confidence: 99%